2011
DOI: 10.1038/nature10427
|View full text |Cite
|
Sign up to set email alerts
|

S-nitrosylation of NADPH oxidase regulates cell death in plant immunity

Abstract: Changes in redox status are a conspicuous feature of immune responses in a variety of eukaryotes, but the associated signalling mechanisms are not well understood. In plants, attempted microbial infection triggers the rapid synthesis of nitric oxide and a parallel accumulation of reactive oxygen intermediates, the latter generated by NADPH oxidases related to those responsible for the pathogen-activated respiratory burst in phagocytes. Both nitric oxide and reactive oxygen intermediates have been implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
488
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 612 publications
(519 citation statements)
references
References 38 publications
11
488
0
3
Order By: Relevance
“…Resistant ecotypes showed a higher expression of AtRbohD and F as well as an earlier accumulation of NO and H 2 O 2 when compared to susceptible ecotypes during interaction with S. sclerotiorum (Perchepied et al, 2010). Adding another layer of complexity to the interplay between NO and ROS, AtRbohD function was shown to be negatively regulated by NO-dependent S-nitrosylation during hypersensitive response (Yun et al, 2011).…”
Section: Ros and Resistance To Fungal Pathogens Of Leavesmentioning
confidence: 97%
“…Resistant ecotypes showed a higher expression of AtRbohD and F as well as an earlier accumulation of NO and H 2 O 2 when compared to susceptible ecotypes during interaction with S. sclerotiorum (Perchepied et al, 2010). Adding another layer of complexity to the interplay between NO and ROS, AtRbohD function was shown to be negatively regulated by NO-dependent S-nitrosylation during hypersensitive response (Yun et al, 2011).…”
Section: Ros and Resistance To Fungal Pathogens Of Leavesmentioning
confidence: 97%
“…Reducing the endogenous NO level using cPTIO or plant mutants impaired in inducible NO production enhanced H 2 O 2 accumulation Tada et al 2004), suggesting that part of the O 2 -produced by NADPH oxidase is scavenged by NO. Yun et al (2011) found that NO abolished AtrbohD activity through S-nitrosylation.…”
Section: Discussionmentioning
confidence: 99%
“…À ce jour, une cinquantaine de protéines S-nitrosylées a ainsi été identifiée, dont une dizaine ont fait l'objet d'études fonctionnelles approfondies (Tableau I). Il ressort de ces études que la S-nitrosylation module l'activité de ces protéines en ciblant directement des résidus Cys de sites actifs [24][25][26][27][28], en promouvant la formation de ponts disulfures [29,30], et en bloquant la fixation de cofacteurs (FAD ou ATP) par encombrement stérique [31,32]. Les données acquises pour les protéines NPR1 (nonexpressor of pathogenesis-related gene 1) et RBOHD (respiratory burst oxidase homologue D) sont détaillées ci-dessous à titre d'exemple (Figure 2).…”
Section: Identification Et Premières Analyses Fonctionnelles Des Protunclassified
“…La plante modèle A. thaliana comporte 10 gènes codant pour des protéines RBOH, l'isoforme AtRBOHD constituant l'une des principales sources de formes actives de l'oxygène en réponse à une attaque pathogène [35]. Récemment, Yun et al [31] ont apporté des arguments en faveur d'un rôle du NO comme régulateur physiologique de l'activité d'AtRBOHD. Plus précisément, ces auteurs ont démontré qu'AtRBOHD est S-nitrosylée in vitro suite à l'exposition de la protéine au GSNO, mais également in vivo lors de l'infection de feuilles d'A.…”
Section: Rbohdunclassified
See 1 more Smart Citation